Neuroimaging in Clinical Practice: An Overview - Rahman, Aminur (Bangladesh Journal of Medicine, 2024)
Neuroimaging is a specialization of imaging technique that produce images of the brain or other parts of the Central Nervous System (CNS) in a noninvasive manner that directly or indirectly assess the structural or functional activity of the nervous system. Computed tomography (CT) and magnetic resonance imaging (MRI) are the most widely used modalities in routine clinical practice. Neuroimaging can be divided into two broad categories, namely, structural and functional neuroimaging. This article discusses the basics and applications of various traditional, as well as emerging neuroimaging techniques, considering their strengths and limitations with this rapidly expanding field. Bangladesh J Medicine 2024; 35: 147-155